2017
DOI: 10.1111/cid.12482
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled clinical trial comparing two dental implants with different neck configurations

Abstract: Both types of implant reported high survival rates and similar bone level changes, clinical parameters, and patient related outcomes after 12 months of loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 45 publications
0
28
0
1
Order By: Relevance
“…The two studies that reported patient‐based MBL changes (Astrand, Engquist, Anzen, et al, ; Sanz‐Martín et al, ) corroborated the findings by presenting a null mean difference between implants with transmucosal collar and two‐piece implants.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…The two studies that reported patient‐based MBL changes (Astrand, Engquist, Anzen, et al, ; Sanz‐Martín et al, ) corroborated the findings by presenting a null mean difference between implants with transmucosal collar and two‐piece implants.…”
Section: Resultsmentioning
confidence: 72%
“…Astrand et al reported peri‐implantitis in 5% of the transmucosal implants. Sanz‐Martín et al () reported the same number of implants affected with peri‐implantitis in both groups.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations